Las fiestas con las guaguas de pan en Obonuco, Nariño, Colombia - Patricia Cerón-Rengifo; Walter Malte Botina; Mauricio Malte Cuaicuán (Antípoda: Revista de Antropología y Arqueología, 2022)
Every summer brings the guaguas de pan (anthropomorphic figures made of wheat flour) festival to southwestern Colombia, with all its castles —or wooden structures covered with bread guaguas—, agricultural products, drinks, and roasted guinea pigs. In the surrounding area, groups of musicians and dancers celebrate to the rhythm of the Sanjuán. This article describes some variations in Obonuco festivities —a village located in this area of Colombia— that took place between the end of the 19th century and 2019. The methodology used included interviews, an audio-visual monitoring of the preparation and celebration of the festival between 2017 and 2019, an analysis of the documents of the Historical Archive of Obonuco, and a review of bibliographic sources. The guaguas de pan festivities clearly illustrate the interrelationships between the local people and the nation state, the Catholic Church, the surrounding villages, and the inhabitants of the city of San Juan de Pasto. The contribution of this article is to show that, in this network of relationships, the nation state has a significant capacity to influence the fiesta’s ways of being its variations over time. This interference of the nation state is heterogeneous, since, on the one hand, it operates in accordance with the national projects of the collectives vying for political power at a given historical moment, and on the other, it is restructured according to the changes in power in world capitalism. Both factors configure particular dynamics in Colombia, in Obonuco and, therefore, in the festivities.